Friedman Curve Positively Correlates with Cesarean Section and Oxytocin Augmentation in Active Phase Delivery as Compared to Partograph: Kurva Friedman Berkorelasi Positif dengan Seksio Sesarea dan Augmentasi Oksitosin pada Fase Aktif Persalinan dibandingkan Partograf - Anak Agung Ngurah Anantasika; I Wayan Artana Putra; Ida Bagus Putra Adnyana; I Wayan Megadhana; Ryan Saktika Mulyana; Agustinus Darmawan Hariyanto (Indonesian Socety of Obstetrics and Gynecology, 2023)
Objective: To investigate the correlation between cesareansection and oxytocin augmentation in childbirth monitoredwith the Friedman curve compared to the World HealthOrganization (WHO) partographs.Methods: An analytic cross-sectional study was conductedfrom March to May 2021, involving mothers giving birthwhose delivery process was monitored using either theFriedman curve or the WHO partograph (n=28 for eachgroup) at Wangaya Hospital in Denpasar City. The durationof the active phase until delivery, occurrence of cesareansection, and administration of oxytocin augmentationwere assessed using the Friedman curve and the WHOpartograph. The normality of the data was tested using theKolmogorov-Smirnov test, and the Spearman correlationtest was employed to measure the direction and strengthof the correlation.Results: There was no signifi cant difference between thegroups in terms of monitoring the active phase until deliveryusing the Friedman curve compared to the WHO partograph(p=1.000 > 0.05). Maternal monitoring with the Friedmancurve showed a positive correlation with the occurrenceof cesarean section compared to the WHO partograph(r=0.296, p=0.027). Additionally, monitoring childbirth withthe Friedman curve exhibited a positive correlation with theadministration of oxytocin augmentation compared to theWHO partograph (r=0.298, p=0.026).Conclusion: The fi ndings suggest a stronger positivecorrelation between the incidence of cesarean section andthe administration of oxytocin augmentation in childbirthmonitored with the Friedman curve compared to the WHOpartograph.Keywords: cesarean section, Friedman curve, oxytocinaugmentation, WHO partograph.AbstrakTujuan: Untuk menentukan korelasi antara operasi sesardan augmentasi oksitosin pada persalinan yang dipantaudengan kurva Friedman dibandingkan dengan partografOrganisasi Kesehatan Dunia (WHO).Metode: Desain penelitian analitik potong lintangdilakukan pada Maret-Mei 2021, dengan melibatkan ibubersalin yang proses persalinannya dipantau menggunakankurva Friedman atau Partograf WHO (n=28 untuk setiapkelompok) di ruang bersalin di Rumah Sakit Wangaya,Kota Denpasar. Waktu fase aktif hingga kelahiran bayi,persalinan seksio sesarea, dan augmentasi oksitosin dinilaidengan menggunakan kurva Friedman dan Partograf WHO.Uji normalitas dilakukan dengan uji Kolmogorov-Smirnov,dilanjutkan dengan uji korelasi Spearman untuk mengukurarah dan kekuatan korelasi.Hasil: Pemantauan ibu bersalin dengan kurva Friedmandibandingkan dengan Partograf WHO dalam hal faseaktif-persalinan bayi menunjukkan tidak ada perbedaanyang signifi kan di antara kedua kelompok (p = 0,000 >0,05). Pemantauan ibu dengan kurva Friedman berkorelasipositif dengan kejadian bedah sesar dibandingkandengan Partograf WHO (r = 0,296, p = 0,027). Selain itu,pemantauan persalinan dengan kurva Friedman berkorelasipositif dengan pemberian oksitosin dibandingkan denganpartograf WHO (r = 0,298, p = 0,026).Kesimpulan: Terdapat korelasi positif yang lebih tinggiantara kejadian bedah sesar dan pemberian augmentasioksitosin pada proses persalinan yang dipantau dengankurva Friedman dibandingkan dengan partograf WHO.Kata kunci: augmentasi oksitosin, kurva friedman, partografWHO, seksio sesarea